Dark Lesions Detection based on Feature Extracted from Retinal Image - Ahmed Hashim Al-Sharfaa, Enas Hamood Al-Saadi, Ali Yakoob Yousif (International Journal of Advanced Science and Technology, 2020)
All Scientific and applied research Emphasizes diabetic retinopathy is the main cause of blindness in people. Bleeding spots are one of the early signs of the disease of diabetic retinopathy. So, the shape bleeding spots and its number are involved in order to identify disease severity. Bleeding spots in color fundus image typically range in size and form, and some even refer to the vasculature of the retinal. the proposed method detect the bleeding spot, its number and size at an early stage, this can be done through the following sequential steps, optic disk localization, detection of macula depending on the location of the optic disk, identification of blood vessels, removal of macula and blood vessels and recognition of bleeding spots by determining the shape, entropy and solidity of all artifacts in the image linked to the identification of bleeding spots, this stage confirms the process of recognition. The proposed method identifies all bleeding spots, and removes them.